Exploring the experiences of having Guillain‐Barré Syndrome: A qualitative interview study. (3rd August 2020) - Akanuwe, Joseph N. A.; Laparidou, Despina; Curtis, Ffion; Jackson, Jennifer; Hodgson, Timothy L.; Siriwardena, Aloysius Niroshan
Abstract: Background: Guillain‐Barré syndrome (GBS) is a rare inflammatory disorder affecting the peripheral nerves. Although typically there is full neurological recovery, some people continue to experience residual physical, psychological or social problems longer term. Evidence describing the experiences of people with GBS is limited. Objective: We aimed to explore the experiences of people with GBS in the UK. Design: We used qualitative (face‐to‐face and telephone) interviews to explore experiences of people with GBS. Audio‐recorded data were transcribed verbatim and analysed using the Framework Method supported by NVivo 11. Setting and Participants: We purposively recruited a sample of 16 volunteers with a prior diagnosis of GBS of varying age, sex, ethnicity, location, marital status, time since diagnosis and length of hospital stay to maximize differences in experience. Interviewees were required to have been discharged from hospital, able to give informed consent, able to speak and understand English and currently resident in the United Kingdom. Results: The key themes arising from the analysis were as follows: the importance of early diagnosis; the experiences of inpatient care; the importance of active support for recovery; the need for communication throughout the course of the illness; the need for greater awareness, knowledge and provision of information by health‐care staff; and path to achieving function. Conclusion: This is the first qualitative study exploring experiences of people with GBS in the UK through their whole illness journey from onset to recovery. The findings contribute to our understanding of the experiences and support needs of people recovering from GBS.